Mediterreanization as a Developmental Phase of Media in Transitional Democracies: Case of Georgia - Maisashvili, Khathouna; Mumladze, Ketevan (European Scientific Journal, ESJ, 2023)
For almost three decades, there has been ongoing analysis of post-communist transitional media as a mutual product of Soviet ideological legacy and Western liberal values in the West, as well as in the post-Soviet sphere. In the transition period, media pluralism has become a common occurrence in contrast with the Soviet period. Reforms directed from the top are rendered arbitrary, and as a result, the unpredictable process gained momentum and was the last straw to end the Soviet Union. What are the specific elements of Mediterraneanization that are clearly expressed in the Georgian reality and what spot should Georgia’s media occupy on the map of systems? To answer this question, emphasis should be placed on specific issues such as the influence of the state and political parties on the media agenda, integration of media and political elites, professionalization of journalism, as well as the sociocultural context of the period of independence. This paper focuses on answering these questions. The present study is the compilation of quantitative and qualitative approaches. 12 media researchers and theoreticians, mainly teachers of Georgian higher education institutions, were selected for the research along with the review of the scientific literature and theory related to the issue. The semi-structured interviews, based on a preliminary questionnaire, were conducted with each researcher. The experts’ responses were processed and compared according to quantitative and qualitative characteristics. Text material was condensed and key messages were highlighted. On the basis of the results, their interpretation and cause-and-effect connection was made.